Growing Student Characters Through Inquiry-Based Science Practicum Module - Sari, Ira Nofita; Octavia, Erna (Universitas Tanjungpura, 2021)
This study aims to determine how the application of inquiry-based science practicum modules to student character. The method used in this research is experimental in the form of a pre-experimental design. The population of this research is the Adventist Junior High School in Singkawang, West Kalimantan. Through the saturated sampling technique, it is known that class VII A is the class used as the experimental class. To find out the student's character, a student character questionnaire was used. This research was conducted during the Covid 19 pandemic so that the learning process was carried out online. Based on the results of data analysis, it is known that in general, the character of students includes honest, hard work, thoroughness and carefulness, creativity, caring for the environment is classified as good.